2001
DOI: 10.1210/jcem.86.4.7433
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Localization of Orexin Receptors in Human Pituitary*

Abstract: Orexins-A and -B are hypothalamic peptides derived from a precursor called prepro-orexin and relationated with the stimulation of food intake. They act on G protein receptors named orexin receptor 1 (OX(1)R) and orexin receptor 2 (OX(2)R), respectively. In the present study, we used RT-PCR and immunohistochemical techniques to detect the presence of OX(1)R and OX(2)R in human pituitary. A band of the expected size for both OX(1)R and OX(2)R was shown in human pituitary by RT-PCR. The cellular localization of O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…RP-HPLC analysis detected orexin-A and orexin-B in rat adenohypophysis, although the amounts were far less than in the median eminence (Date et al, 2000b). On the other hand, intraventricular injections of orexins stimulate the liberation of gonadotropins (Pu et al, 1998) and ACTH (Kuru et al, 2000) and inhibit the secretion of LH, prolactin (Kohsaka et al, 2001) and GH (Blanco et al, 2001;Seoane et al, 2004;Molik et al, 2008). Recent data suggest that these neuropeptides also increase the production of glucocorticoids in rats and humans (Spinazzi et al, 2006), being implicated in processes of stress produced after the activation of the hypothalamic orexinergic cells by CRF (Winsky-Sommerer et al, 2004).…”
Section: Localization Of Orexin-ir Fibers In the Brain Of Vertebratesmentioning
confidence: 99%
“…RP-HPLC analysis detected orexin-A and orexin-B in rat adenohypophysis, although the amounts were far less than in the median eminence (Date et al, 2000b). On the other hand, intraventricular injections of orexins stimulate the liberation of gonadotropins (Pu et al, 1998) and ACTH (Kuru et al, 2000) and inhibit the secretion of LH, prolactin (Kohsaka et al, 2001) and GH (Blanco et al, 2001;Seoane et al, 2004;Molik et al, 2008). Recent data suggest that these neuropeptides also increase the production of glucocorticoids in rats and humans (Spinazzi et al, 2006), being implicated in processes of stress produced after the activation of the hypothalamic orexinergic cells by CRF (Winsky-Sommerer et al, 2004).…”
Section: Localization Of Orexin-ir Fibers In the Brain Of Vertebratesmentioning
confidence: 99%
“…Recently, we have demonstrated by RT-PCR and immunohistochemistry the localization of orexin receptors in human pituitary gland (Blanco et al 2001). With double immunofluorescence we demonstrated that OX 1 R is expressed in somatotroph cells and that OX 2 R is found in corticotrophs.…”
Section: Discussionmentioning
confidence: 78%
“…More recently, the expression of orexin receptors in peripheral tissues, such as the rat and human adrenal gland (Lopez et al 1999;Blanco et al 2002) and the human pituitary (Blanco et al 2001), was demonstrated by RT-PCR and immunohistochemistry. Similarly, the presence of orexins in various tissues including posterior lobe of rat pituitary (Date et al 2000), pineal gland (Mikkelsen et al 2001), pancreas, intestinal mucosa (Kirchgessner and Liu 1999), and stomach (Sanchez de Miguel and Burrel 2002) was also reported.…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of publications indicate that orexin neuropeptides are also involved in endocrine regulation via the hypothalamo-pituitary axis [2,9,48,49,50]. Regulation of the sympathetic system [64,125], thermogenesis and the hypothalamo-pituitary axis is consistent with orexin's proposed roles in promoting wakefulness and metabolic rate [128].…”
Section: Orexins and Energy Homeostasis: In Light Of Narcolepsymentioning
confidence: 78%